Representation of subaltern women in Pad Man: Against the silencing of women's rights and voices - Suandi, Susnita Leoni (NOTION: Journal of Linguistics, Literature, and Culture, 2024)
In patriarchal silence, "Pad Man" defends oppressed voices. The film reveals inequalities and promotes societal change. This study uses Gayatri Spivak's postcolonial review to examine subaltern women's portrayal. This qualitative study analyzes the story and visuals of "Pad Man," which represents subaltern Indian people and their struggles. We selected movie sequences and examined their characters, narratives, and messages for research. This study discovered various evidence of patriarchal culture's oppression of women in India and limited access to women. "Pad Man" portrays women within patriarchal culture, highlights societal stigma, and advocates for women's liberation. This film also addresses India's reproductive health information gap. This film empowers subalterns, especially in India, by telling their experience. This examination also scrutinizes the film's impact on societal awareness, transformation, and gender equality.